SAÚDE SEXUAL E SEXUALIDADE DE MULHERES IDOSAS: REVISÃO DE LITERATURA - dos Santos, Dayane Luizy Ribeiro (2017)
Objective: To identify in literature the generalpoints raised about sexual health and sexualityamong older women. Methods: This is aLiterature Review from published studies onthe theme with the following inclusion criteria:full Article available in the databases LILACSand MEDLINE, published between 2005-2015, in Portuguese, English or Spanish.Results: We sampled 26 articles, with apredominance of articles from Brazil and theUnited States. Themes were grouped asfollows: sexuality and prevention of sexuallytransmitted diseases; sexuality and sexual life;sexual desire, eroticism and self-image;approaches and influence of cancer onsexuality, sex education and sexual self-care,and attention of health care professionals to thesexuality of elderly women. Conclusion: Thetheme remains a taboo in all parts of the world,and health professionals need to discuss sexand sexuality more naturally and clearlyinclude it in the context of health assessment of the elderly.